A Study of Relationship between Locus of Control and Self-monitoring to Resilence in Students - Shanava, Ina; Gergauli, Giorgi (European Scientific Journal, ESJ, 2022)
A person experiences both positive and negative stress during his life, the influence of which is mainly associated with a wide range of negative consequences, such as a decrease in well-being, an increase in diseases, post-traumatic stress, anxiety and depression disorders. However, it should be noted that high stress in a person does not always develop these kinds of negative results. According to the latest researches and studies, most of the people are exposed to be stable to the stress, thus, the main factor in order to cope with the unpredictable environment, is to develop resilience (Troy&Mauss). Given that the ability to disengage from negative stimuli, including one’s own negative feelings, is an important protective factor against long-term negative results, resilience represents the ability of a person to cope with life’s difficulties. Resilience, as a multidimensional characteristic, varies by context, age, gender, culture, and individual life (Felicia et al. 2021). According to the contemporary approaches, resilience is a personal trait, that helps a person to adapt and cope with traumatic experience. Psychological component of resilience means that a person manages to maintain psychological health without any trauma and stressors, while, behavioral component of resilience means maintenance of self-effectiveness and aspiration towards goals (Kamushadze, 2021). One of the components of resilience at the individual level is identified as self-control, which is an aspect of behavior control and is often viewed as willpower and the ability to control impulses. In a psychological sense, self-control refers to emotions and the initiation or modification of emotional reactions through cognitive processes. The locus of control is also considered to be a factor that has a significant influence on the formation of resilience. According to Rotter, people differ from each other according to the localization of control over events, of which 2 poles are differentiated - internal and external. Internal people believe that everything that happens in their lives depends only on their personal qualities - purposefulness, abilities and competence. While, external people strongly believe that their lives are controlled by outside forces, they think that their success or unsuccess is fault of randomness, other people and so on. Any person takes a special position on this locus of control continuum, which is created with these two poles. Considering abovementioned information, this paper aims at determiningbetween Locus of control and self-monitoring, resilience among students. Internal-External Locus of Control Scale (I-E Scale), Self – Monitoring Scale, Brief Resilience Scale (BRS) – were used. Based on the analysis of the results, it was revealed that self-ownership is related to resilience and locus of control, and the latter is negatively related to resilience. Differences were analyzed by demographic characteristics.